Wind tunnel installation effects on a high-speed exhaust flow under large blockage - Tsentis, Spyros; Goulos, Ioannis; Debiasi, Marco; Prince, Simon A.; Pachidis, Vassilios; Zmijanovic, Vladeta; Saavedra, Josè (American Institute of Aeronautics and Astronautics (AIAA), 2025)
This study presents a numerical investigation of wind tunnel installation effects on the exhaust flow for a high-speed system under a blockage ratio of 16.5%. The configuration features a nozzle and a cavity embedded at the base of an ogive-cylindrical body and is representative of future, high-speed exhausts. The work is motivated by the need of testing large, powered-on models and the size of most closed transonic tunnels available in academic research facilities. This combination leads to high blockage ratios and therefore severe flow distortion. The objective is to examine the installation effects and quantify the base flow similarity relative to unbounded conditions. The numerical approach is validated against experimental data. A jet vectoring effect is identified due to the pylon, which is intensified under choked tunnel operation. Additionally, a methodology is proposed, which allows base pressure to be compared to unbounded flow conditions. Results show that the pressure distribution agrees within 1.5% and 0.1% for the base and cavity walls, respectively. This demonstrates that local aerodynamic similarity can be established between large-blockage, tunnel-tested conditions and unbounded flow through the proposed approach. This enables the use of small-scale facilities for base flow studies of high-speed exhausts under large blockage.
Keywords: Aerospace & Aeronautics; 4001 Aerospace engineering